2014
DOI: 10.14814/phy2.12087
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose maternal alcohol consumption: effects in the hearts of offspring in early life and adulthood

Abstract: High alcohol consumption during pregnancy leads to deleterious effects on fetal cardiac structure and it also affects cardiomyocyte growth and maturation. This study aimed to determine whether low levels of maternal alcohol consumption are also detrimental to cardiomyocyte and cardiac growth in the early life of offspring and whether cardiac structure and function in adulthood is affected. Pregnant Sprague–Dawley rat dams were fed a control or 6% (volume/volume) liquid‐based ethanol supplemented (isocaloric) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…In sheep studies of maternal obesity, an accumulation of collagen was also reported [110]. Nguyen et al[111] found cardiac fibrosis in the adult offspring exposed to chronic alcohol consumption during gestation. The presence of cardiac fibrosis is an important determinant of abnormal myocardial stiffness that contributes to diastolic dysfunction [112].…”
Section: Discussionmentioning
confidence: 92%
“…In sheep studies of maternal obesity, an accumulation of collagen was also reported [110]. Nguyen et al[111] found cardiac fibrosis in the adult offspring exposed to chronic alcohol consumption during gestation. The presence of cardiac fibrosis is an important determinant of abnormal myocardial stiffness that contributes to diastolic dysfunction [112].…”
Section: Discussionmentioning
confidence: 92%
“…Animal models involving sheep and mice have been subjected to three different models of alcohol exposure: single occasion binge drinking, ad hoc low‐to‐moderate chronic intake throughout pregnancy and periconceptional exposure before implantation. These experiments showed that all three models had an impact on the development of adult diseases, namely cardiovascular diseases such as hypertension and poorer cardiac recovery after ischaemia, metabolic diseases, including high fasting glucose and insulin, insulin resistance and obesity worsened by a second hit mechanism due to a high‐fat diet, and renal malfunction, defined as inability to concentrate urine .…”
Section: Epigenetic Effectsmentioning
confidence: 99%
“…Growth : Sprague-Dawley rats were fed a liquid diet with or without 6% v/v alcohol throughout gestation, and growth patterns were studied in the offspring up to 1 year; slower growth was detected in males from alcohol-fed dams between 7 and 12 months of age, whereas no differences were found in females (Probyn et al, 2012). Cardiac : Using a low level of 6% v/v alcohol during pregnancy, it was discovered that gene expression of a number of cardiac growth factors in the rat fetus (harvested on gestation day 20) and cardiomyocyte number in weanling offspring (postnatal day 30) were not altered by alcohol, whereas at 8 months age, there were significant increases in left ventricle anterior and posterior wall thickness during diastole in alcohol-exposed offspring (Nguyen et al, 2014). Thyroid : Prenatal alcohol effects on adult thyroid function have been studied in a rat model after 5% (w/v) alcohol was fed during pregnancy.…”
Section: Prenatal Alcohol-induced Adult Onset Diseasesmentioning
confidence: 99%
“…It is possible that higher doses of alcohol would lead to birth defects as well as adult-onset diseases, whereas lower doses of alcohol may result in subtle alterations that may not show any visible phenotypes at birth, but would nevertheless result in increased vulnerability to adult-onset disease states (Nguyen et al, 2014). Moreover, early gestation alcohol exposure is likely to produce adverse effects on diverse organs systems, whereas late gestation alcohol exposure is likely to result in tissue- and cell type-specific effects (Waterland and Michels, 2007) and the consequent adult disease outcomes are likely to be different.…”
Section: Directions For Fasd-dohad Fieldmentioning
confidence: 99%